Implementing Student Tolerance and Patriotism Through Learning History of National Movements - Muslim Muslim; Warto Warto; Djono Djono (Indonesian Academy of Social and Religious Research (IASRR), 2020)
This study aims to obtain: (1) inculcating the values ​​of tolerance and patriotism of students through learning the history of the national movement, (2) difficulties experienced by history teachers, and (3) efforts made by history teachers to overcome these difficulties. This study uses qualitative methods, with a single embedded case study strategy. This study was conducted at SMA Negeri 11 Yogyakarta. Data were collected through observation, in-depth interviews, and document study. The data analysis technique used the interactive model of Miles and Huberman's analysis. The results of the study show that: (1) Inculcating the values ​​of tolerance and patriotism in students, namely through learning preparation, learning implementation, (using the discussion method, because in discussions it is easy to instill the values ​​of tolerance and patriotism in students), and evaluation (2) The difficulty faced by history teachers is that they have little time to study, and currently online learning makes it difficult for teachers to socialize with students. (3) Efforts made by history teachers, in overcoming these difficulties, were to make themselves role models and motivators for their students. In the end, after the obstacles were overcome, the students' tolerance and patriotism values ​​increased.